Identifikasi Penguasaan Konsep Materi Hukum Archimedes dan Hukum Pascal Berbantuan Quizizz - Faradila Nur Anjelin; Fatmatul Ailiyah; Bakhrul Rizky Kurniawan; Mimin Nurul Kholifah (-)
This article aims to reveal the mastery of concepts activated by respondents when answering questions related to Pascal's law and Archimedes law. This study used a survey method with a test instrument of 10 multiple choice questions on the topic of static fluids using Quizizz. The subjects used to research were physics students from semester 6 to high school students who had received static fluid material. The research was conducted online with a period of 10 days and obtained 34 respondents. The data analysis techniques used were quantitative and qualitative analysis with 51% of the results obtained showed that students were still low in mastering the concept of Pascal's law and Archimedes' law.